Multidimensional Vascularized Polymers using Degradable Sacrificial Templates. (17th December 2014) - Gergely, Ryan C. R.; Pety, Stephen J.; Krull, Brett P.; Patrick, Jason F.; Doan, Thu Q.; Coppola, Anthony M.; Thakre, Piyush R.; Sottos, Nancy R.; Moore, Jeffrey S.; White, Scott R.
Abstract : Complex multidimensional vascular polymers are created, enabled by sacrificial template materials of 0D to 3D. Sacrificial material consisting of the commodity biopolymer poly(lactic acid) is treated with a tin catalyst to accelerate thermal depolymerization, and formed into sacrificial templates across multiple dimensions and spanning several orders of magnitude in scale: spheres (0D), fibers (1D), sheets (2D), and 3D printed. Templates are embedded in a thermosetting polymer and removed using a thermal treatment process, vaporization of sacrificial components (VaSC), leaving behind an inverse replica. The effectiveness of VaSC is verified both ex situ and in situ, and the resulting structures are validated via flow rate testing. The VaSC platform is expanded to create vascular and porous architectures across a wide range of size and geometry, allowing engineering applications to take advantage of vascular designs optimized by biology. Abstract : Sacrificial templates of 0D to 3D are fabricated and used to create vascular and porous architectures. Embedded sacrificial templates are removed using a thermal treatment process, vaporization of sacrificial components (VaSC), leaving behind an inverse replica. The effectiveness of VaSC is verified both ex situ and in situ, and the resulting structures are validated via flow rate testing.